Strategi Komunikasi Haifa Montessori Islamic School Dalam Membangun Brand Image - Sakinah, Nurul (Universitas Al Azhar Indonesia, 2024)
Providing the best education is the goal of every parents especially kindergarten. Sending children to kindergarten school nowadays is the best consideration for many parents to shape their character in their golden age. Thus, this can be an opportunity for any entepreneur who runs a business in early childhood education field to establish a school with a different and unique studying method. Therefore, an appropriate marketing communication strategy is required the school business will be known to the public, especially the parents. Furthermore, it is substantial for schools to create a positive image so it will obtain parents trust. The objective of this research is observing the marketing communication strategy conducted by Haifa Montessori Islamic School by employing Integratede Makreting Communication which focuses on five elements, online & social media marketing, advertising, personal selling and direct & database marekting. The research method is qualitative, data collected by doing an interview and including documentation. The result of the research shows that Haifa implements organic marekting and the used media to do a marketing communicaion is media sosial, Facebook and Instagram. Instagram is more effective to gain massive audience. Other than that, Haifa wants to have an image as a school that is able to building and develop students character. In addition, Haifa fulfills the brand image indicators, namely, corporate image, product image and user image.